Outcome of Allogeneic Hematopoietic Stem Cell Transplantation in Adult Patients with Philadelphia Chromosome-Positive Acute Lymphoblastic Leukemia in the Era of Tyrosine Kinase Inhibitors: A Registry-Based Study of the Italian Blood and Marrow Transplantation Society (GITMO) - Anna Candoni; Alessandro Rambaldi; Renato Fanin; Andrea Velardi; William Arcese; Fabio Ciceri; Davide Lazzarotto; Federico Lussana; Jacopo Olivieri; Giovanni Grillo; Matteo Parma; Benedetto Bruno; et al. (2019)
We performed a nationwide registry-based analysis to describe the clinical outcome of adult patients with Philadelphia chromosome-positive acute lymphoblastic leukemia (Ph+ ALL) who underwent an allogeneic hematopoietic stem cell transplantation (HSCT) after a tyrosine kinase inhibitor (TKI)-based treatment A total of 441 patients were included in the study. The median age at HSCT was 44 years (range, 18 to 70 years). All 441 patients (100%) received TKI before HSCT (performed between 2005 and 2016). Of these 441 patients, 404 (92%) were in cytologic complete remission (CR), whereas the remaining 37 (8%) had active disease at the time of HSCT. Molecular minimal residual disease (MRD) was negative in 147 patients (36%) at the time of HSCT. The donor was unrelated in 46% of patients. The most prevalent source of stem cells was peripheral blood (70%). The conditioning regimen was myeloablative in 82% of cases (total body irradiation-based in 50%) and included antithymocyte globulin in 51% of patients. With a median follow-up after HSCT of 39.4 months (range, 1 to 145 months), the probability of overall survival (OS) at 1, 2, and 5 years was 69.6%, 61.1% and 50.3%, respectively, with a median OS of 62 months. Progression-free survival (PFS) at 1, 2, and 5 years was 60.2%, 52.1% and 43.7%, respectively. OS and PFS were significantly better in patients who were in CR and MRD-negative at the time of HSCT compared with patients who were in CR but MRD-positive (50% OS not reached versus 36 months; P = .015; 50% PFS not reached versus 26 months, P = .003). The subgroup of MRD-negative patients both at HSCT and at 3 months after HSCT had a better outcome (5-year OS, 70%). Conversely, the 37 patients who underwent a HSCT with active Ph+ ALL had a median OS of 7 months and a median PFS of 5 months. The 5-year cumulative incidence of relapse was significantly lower in MRD-negative patients (19.5% versus 35.4%; P = .001). Nonrelapse mortality (NRM) after 1, 2, and 5 years was 19.1% (95% confidence interval [CI], 15.5% to 22.9%), 20.7% (95% CI, 17% to 24.7%), and 24.1% (95% CI, 20% to 28.5%), respectively. NRM was significantly lower with a modified European Society for Blood and Marrow Transplantation (mEBMT) risk score of 0 to 2 compared with ≥3 (15% versus 25%; P = .016). The median OS for Ph+ ALL patients who underwent a TKI-based treatment followed by an allogeneic HSCT, in recent years at the GITMO centers, was 62 months. Evaluation of the mEBMT risk score can be useful to predict NRM. Our data confirm that HSCT is a potentially curative treatment for Ph+ ALL with an excellent outcome for the subgroup of MRD-negative patients both at HSCT and at 3 months after HSCT (5-year OS, 70%).